(untitled) - Beil, Frank J (Business Expert Press, 2013)
Ebook from IG Library ; Derivatives, and derivatives used to hedge financial and operating functions, are designed to allow managers of firms to manage effectively the downside risk of their financial and operating strategies. They also can be very useful tools that allow managers and executives to accurately predict financial and operational performance and manage the investment communities' 'expectations' regarding overall firm performance. Derivatives and hedges, however, if not properly designed in conjunction with the firm's risk management strategy, can be potentially disastrous for the firm. The ongoing financial turmoil in markets can be partially explained by company managers and executives not understanding the potential financial statement impact when derivative markets move in a particular direction for longer periods of time than anticipated by firms. This book is designed for managers and executives to be a comprehensive yet accessible resource for understanding the impact of derivative and hedge accounting on a company's reporting of financial statements. The book's primary purpose is to demystify derivatives and provide practical advice and counsel on how to use them to manage more effectively the operational and financial risk to the firm. When used properly derivatives are an extremely effective tool that managers and executives can use to reduce uncertainty regarding the future.
Keywords: Financial Accounting and Auditing; Kế toán kiểm toán; Điều hành và quản lý nhân sự